PENGEMBANGAN STRATEGI PEMASARAN KERIPIK PISANG PADA INDUSTRI RAJA BAWANG DI KOTA PALU - Matantu, Irene Lisa; Lamusa, Arifuddin (AGROTEKBIS, 2018)
Raja Bawang Industry is one of the business that produce banana chips, the industry is located in Jalan Abdul Rahman Saleh No. 33 Palu. This study aimed to analyze the internal and external factors faceing Industry of Raja Bawang in the development of marketing strategies of banana chips; to analyze the development of marketing strategies of banana chips at Raja Bawang Industry. The total value obtained from IFAS table is equal to 1.15 with a score of 2.15 strengths and weaknesses score of 1.00. This shows that the power factor at Raja Bawang Industry is greater than a factor of weakness, while the total value obtained from EFAS is 3.54 with a score of 2.1 opportunities and threats score of 1.44. This shows that the chance factor which is owned by Raja Bawang Industry is greater than a factor of threats. Based on the calculations of the value of internal rating and value of factors for developing marketing strategy banana chips as the X-axis is 1.15, while external factors on Raja Bawang Industry as the Y-axis is 0.66. The results of this study indicate that business conditions in the industry of banana chips of Raja Bawang currently in quadrant I, which in this position is a position that is favorable for the industry because the industry can create a strategy to use force to take advantage of existing opportunities. Keywords: Banana chips, SWOT analysis, Strategy development.